Antimicrobial susceptibility pattern of pathogenic bacteria of Chronic Suppurative Otitis Media (CSOM) patients through culture and sensitivity in a tertiary level hospital in Khulna (Mediscope, 2020)
Background: Chronic Suppurative Otitis Media (CSOM) is a chronic disease associated with irreversible consequences and serious intracranial and extracranial complications. Thereby early & effective treatment must be needed to avoid such complications.Objectives: This study was carried out to know antimicrobial susceptibility pattern of pathogenic bacteria through culture and sensitivity for better management and to reduce resistance & morbidity due to CSOM.Methods: After taking proper approval from hospital administration, this study was conducted on 82 patients of clinically diagnosed cases of both Tubo-tympanic & Attico-antral variety of CSOM attending ENT OPD of Gazi Medical College Hospital, Khulna from January 2018 to June 2018. After proper sample collection by sterile aural swabs, they were immediately sent to the microbiology laboratory of Gazi Medical College Hospital, Khulna for bacterial culture, isolation and identification. Routine antibacterial susceptibility was done as per CLSI guidelines. SPSS 18.0 was used for statistical analysis.Results: The commonest pathogens isolated were Staphylococci, Coagulase Negative Staphylococci (CONS), Pseudomonas aeruginosa, Klebsiella spp. & others; mostly showing susceptibility to high end antibiotics like Ceftriaxone and Amoxiclav for staphylococcal infection & piperacillin-tazobactum for Pseudomonal infection.Conclusion: Antibiotic sensitivity pattern determines the prevalent bacterial organism causing CSOM to start empirical treatment for a successful outcome, and thus to prevent the emergence of resistant strains.Mediscope Vol. 7, No. 1: Jan 2020, Page 1-6